2020
DOI: 10.1155/2020/9605950
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Models for Estimating Solar Radiation from Sunshine Duration in Croatia

Abstract: The performance of seventeen sunshine-duration-based models has been assessed using data from seven meteorological stations in Croatia. Conventional statistical indicators are used as numerical indicators of the model performance: mean absolute percentage error (MAPE), mean bias error (MBE), mean absolute error (MAE), and root-mean-square error (RMSE). The ranking of the models was done using the combination of all these parameters, all having equal weights. The Rietveld model was found to perform the best ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Moreover, in Croatia [35], a research study concentrated on several models that are used for estimating solar radiation. www.ijacsa.thesai.org These models assessed based on seven meteorological stations dataset, where the models studied, compared and evaluated to find out the best accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, in Croatia [35], a research study concentrated on several models that are used for estimating solar radiation. www.ijacsa.thesai.org These models assessed based on seven meteorological stations dataset, where the models studied, compared and evaluated to find out the best accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…All these methods represent more than 294 models around the world [38]. Recently, to find the valid estimation model for a site, several comparison works have been carried out, such as Betti et al's work in Croatia [39], Wang et al's work [40] in China, and Chukwujindu's work in Africa [32].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, the sunshine-based models were more accurate than the temperature-based models and the BC model is recommended to estimate both daily and monthly average daily when only temperature data are available. Tihomir et al (2020) [10] assessed the performance of seventeen sunshine-duration-based models at Croatia. The study found that the Rietveld model was found to perform the best overall, followed by Soler and Dogniaux-Lemoine monthly dependent models.…”
Section: Introductionmentioning
confidence: 99%